EmpathyAut: An Empathy Map for People with Autism - Melo, Áurea Hiléia da Silva; dos Santos, Jonathas Silva; Cabrejos, Luis Jorge Henrique Rivero; Barreto, Raimundo da Silva (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
When developing software for autistic people, the design techniques have to ensure that the physical and cognitive conditions do not prevent the interaction with the software. Empathy Map is an important tool for most of interface projects. However, the tool’s components related to “Listen”, “Think and Feel”, “See”, and “Say” may be problematic for autistic users with low/medium degree of functioning, therefore requiring adaptation. This is due to cognitive impairment and limitations caused by this disorder on verbal communication. To address these issues, this work presents the initial proposal of EmpathyAut which is based on the traditional Empathy Map model, but has sections that are more compatible with the reality of autistic people. The main EpathyAut goal is to improve empathy between the interface designers and autistic users. The EmpathyAut covers the autistic people’s main affected areas, namely interaction, communication, behavior, and cognition.